Development of chitosan nanoparticles loaded with summer savory (Satureja hortensis L.) essential oil for antimicrobial and antioxidant delivery applications - Feyzioglu, G. Cansu; Tornuk, Fatih (ELSEVIER, 2016)
The aim of this study was to produce novel water-soluble and thermally stable chitosan nanoparticles (NPs) loaded with different levels (1%, 1.2%, 1.4% and 1.5%) of summer savory (Satureja hortensis L.) essential oil (EO) using ionic gelation method and to determine their characteristic properties. NP samples with diameters ranging from 140.25 nm to 237.60 nm were obtained at pH levels of 4.5, 6.0 and 10.0. Zeta potential values of the NPs were found to be negative (-7.54 to -21.12 mV). Encapsulation efficiency (EE) was in the range of 35.07-40.70%. EO loaded NPs exhibited strong antibacterial (against Staphylococcus aureus, Listeria monocytogenes and Escherichia coli O157:H7) and DPPH scavenging activity dependently to the concentration of EO encapsulated. SEM images demonstrated the spherical shapes of the chitosan NPs. In conclusion, summer savory EO loaded chitosan NPs that were highly adapted to excessive environmental factors such as acidic pH and high temperature and with high bioactive properties were successfully fabricated convenient for future food processing and packaging applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Chitosan nanoparticles; Summer savory essential oil; Antimicrobial; Antioxidant; Nanoencapsulation; ENCAPSULATION; NANOCAPSULES; IMPROVEMENT; STABILITY; EXTRACT; EUGENOL; ACID; Food Science & Technology